LEKSIKON LINGKUNGAN KELAUTAN DALAM BAHASA MELAYU NATUNA DI DESA SEPEMPANG: KAJIAN EKOLINGUISTIK - Septianengrum, Dwi; Sulissusiawan, Ahadi; Syahrani, Agus (Universitas Tanjungpura, 2024)
This research discusses the issue of lexicon form, lexical meaning, and lexicon function in the marine environment of Sepempang Village, Natuna Regency. The aim of this research is to identifiy the form of the lexicon in the form of flora, fauna, and marine environmental facilities and infrastructure, then describe them based on lexical meaning and language function. The method used in this research is a descriptive method in qualitative form. The data source in this research is the community around Sepempang Village who are native speakers of Natuna Malay. Data collection techniques in this research use direct techniques, namely observation, interviews, notes, recording, and documentation. This research produced 80 forms of marine environmental lexicon, in the form of 8 flora lexicons, 62 fauna lexicons, and 10 marine activity facilities and infrastructure lexicons. The lexical meanings identified in this study based on word forms found 58 monomorphemic forms and 22 phrase forms. The lexicon functions found are based on 80 lexicons forms, there are four fauna lexicon functions, comsisting of 2 imaginative function lexicons, 1 personal function lexicon, and 1 combined imaginative and personal lexicon.